“Diatomik" - new thermal insulating material for road construction in the conditions of cryolithic zonE - E. A. Korotkov; A. O. Konstantinov; A. A. Melnikova; K. S. Ivanov (Вестник СибАДИ)
There are considered prospects of using new material "DIATOMIK" in road construction in the conditions of Far North. The offered material is compared to foreign analogs. By means of modern software there is made a thermal interaction’s prospect of frozen soil and a road construction with a thermal insulating layer of material in the basis.